Pigmentary demarcation lines: a clinical profile of 50 subjects and report of new pattern of pigmentation observed - Antony, Anju; Kumar, Pramod (International Journal of Research in Dermatology, 2018)
Background: Pigmentary demarcation lines (PDL) correspond to a border of abrupt transition between the more deeply pigmented skin of the outer surfaces and the lighter inner surfaces. On the basis of their location they have been classified into eight types, type A to type H. The present study is an attempt to obtain a better understanding of the clinical types of pigmentary demarcation lines in Indians, and to report any previously undescribed patterns of pigmentation. Methods: Patients attending the Outpatient Department for various complaints were examined for the presence of pigmentary demarcation lines, and those with pigmentary demarcation lines were analysed further. Results: 50 subjects of Fitzpatrick skin types 4 and 5, with pigmentary demarcation lines were examined in detail. The various types of pigmentary demarcation lines seen were Type A (38%), Type B (14%), Type C (24%), Type F (22%), Type G (4%), Type H (4%). All types were more common in females with the exception of Type C, which was observed only in males. Type D and Type E PDL were not observed in any of the subjects screened. Conclusions: The most common type of PDL observed in our study was Type A PDL, followed by Type C PDL. The youngest subject was 2 years old, the oldest was aged 75.The majority were seen in adults; Type A and Type C PDL were the common types seen in children. A family history of PDL was present in 5 (10%) and all were females. A hitherto undescribed pigmentary demarcation line is also described along with this study.